Co-Regulation of Histone-Modifying Enzymes in Cancer - Islam, Abul B. M. M. K. (Public Library of Science, 2011)
Cancer is characterized by aberrant patterns of expression of multiple genes. These major shifts in gene expression are believed to be due to not only genetic but also epigenetic changes. The epigenetic changes are communicated through chemical modifications, including histone modifications. However, it is unclear whether the binding of histone-modifying proteins to genomic regions and the placing of histone modifications efficiently discriminates corresponding genes from the rest of the genes in the human genome. We performed gene expression analysis of histone demethylases (HDMs) and histone methyltransferases (HMTs), their target genes and genes with relevant histone modifications in normal and tumor tissues. Surprisingly, this analysis revealed the existence of correlations in the expression levels of different HDMs and HMTs. The observed HDM/HMT gene expression signature was specific to particular normal and cancer cell types and highly correlated with target gene expression and the expression of genes with histone modifications. Notably, we observed that trimethylation at lysine 4 and lysine 27 separated preferentially expressed and underexpressed genes, which was strikingly different in cancer cells compared to normal cells. We conclude that changes in coordinated regulation of enzymes executing histone modifications may underlie global epigenetic changes occurring in cancer.